(untitled) (Homoeopathy for All, 2024)
Even in this age of heightened consumer consciousness, the health care industry remains a source of concern. This is particularly true regarding the extent and quality of information provided to patients and health professionals by the pharmaceutical industry. Labeling medicines in India is an important aspect of ensuring patient safety and compliance with regulatory requirements. The label of over-the counter (OTC) medicines plays a crucial role in conveying valuable information to the patient for safe and effective use. A survey of the labeling information provided for Ayush drugs, especially ayurvedic drugs, marketed in India highlights the importance of accurate and clear labeling for these traditional medicines. Correct drug labeling is central for ensuring proper drug dispensing and thus for patient safety. Labeling errors may result in adverse health outcomes. A study by Shah el al show highlights the lacunae in the contents of the labeling of drugs and recommends strict enforcement of Drugs Act for better and safer use of medicines.